Evaluating effect of symptoms heterogeneity on decision‐making ability in obsessive–compulsive disorder. Issue 7 (9th February 2015) - Martoni, Riccardo Maria; Brombin, Chiara; Nonis, Alessandro; Salgari, Giulia Carlotta; Buongiorno, Angela; Cavallini, Maria Cristina; Galimberti, Elisa; Bellodi, Laura
<x xml:space="preserve">Abstract</x> Aims Despite having a univocal definition, obsessive–compulsive disorder (OCD) shows a remarkably phenotypic heterogeneity. The published reports show impaired decision‐making in OCD patients, using tasks such as the Iowa Gambling Task (IGT). We wanted to verify the hypothesis of an IGT worse performance in a large sample of OCD patients and healthy control (HC) subjects and to examine the relation between neuropsychological performance in IGT and the OCD symptoms heterogeneity. Methods Binary data from the Yale–Brown Obsessive Compulsive Scale collected on a large sample of OCD patients were analyzed using a multidimensional item response theory model to explore the underlying structure of data, thus revealing latent factors. Factor scores were categorized into quartiles. Then, for each factor, we identified patients respectively with the highest versus lowest score. We evaluated whether symptom dimensions affect the probability of a correct answer over time generalized, during IGT performance, fitting a generalized linear mixed model. Results We found a general deficit in ambiguous decision‐making in OCD compared to HC. Moreover, our findings suggested that OCD symptoms heterogeneity affects decision‐making learning abilities during IGT. In fact, while 'Symmetry' and 'Washing' patients showed a learning curve during the task, other subgroups did not. Conclusions Our study confirmed previous findings suggesting that OCD is characterized by a deficit in decision‐making under uncertainty. Moreover, our study gave evidence about biological specificity for each symptom dimension in OCD. Data were discussed in the context of the somatic marker hypothesis, which was hypothesized to be reduced in OCD patients.